2015
DOI: 10.3390/systems3030062
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Multi-Level Governance and Wicked Problems in Urban Transportation Systems: The Case of Palermo Municipality

Abstract: Italian New Public Management (NPM) has been mainly characterized by a political orientation toward power decentralization to local governments and privatization of public companies. Nowadays, local utilities in Italy are often run by joint stock companies controlled by public agencies such as Regional and Municipal Administrations. Due to this transformation, these companies must comply with a set of diverse expectations coming from a wide range of stakeholders, related to their financial, competitive and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Others studies that applied System Dynamics to urban transportation issues may be found in Wang et al (2008), Armah et al 2010, Haghshenas et al (2015) and Noto and Bianchi (2015). Analysing this contribution, it emerges how this methodological approach is suitable in order to adopt a sustainable perspective.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Others studies that applied System Dynamics to urban transportation issues may be found in Wang et al (2008), Armah et al 2010, Haghshenas et al (2015) and Noto and Bianchi (2015). Analysing this contribution, it emerges how this methodological approach is suitable in order to adopt a sustainable perspective.…”
Section: Methodsmentioning
confidence: 98%
“…This approach empowers a systemic view of transportation systems, since each performance driver shows how the employment of the linked strategic resources affects all the other interdependent resources within the system (Noto and Bianchi 2015). Due to this interdependence, each strategic resource has the power to foster others in the same system, or not.…”
Section: Methodsmentioning
confidence: 99%
“…Future research could concentrate also on MREM in other countries than Poland and The Netherlands. In further research, it can also be interesting to add other sources about NPM and GG, like Gruening [54], Noto & Bianchi [55] and the Council of Europe [56]. By adding more perspectives on NPM and GG, the questionnaire can be modified and it can contribute to the refinement of the operationalization of the NPM and GG principles.…”
Section: Good Governancementioning
confidence: 99%
“…In particular, the goal of externalisation is to improve performance in the provision of public services, increase service quality and lower costs. In order to meet these expectations and goals, it becomes critically important for each partner to define which type of governance form should be involved (Broadbent et al, 2003;Rosenau, 2000;Noto & Bianchi, 2015). efficiency levels has been developed, using the Data Envelopment Analysis (DEA) (Charnes et al, 1978;Fare et al, 1978) non-parametric technique in a modified Slack Based Measure (SBM), (Tone, 2001; version.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the goal of externalisation is to improve performance in the provision of public services, increase service quality and lower costs. In order to meet these expectations and goals, it becomes critically important for each partner to define which type of governance form should be involved (Broadbent et al, 2003; Rosenau, 2000;Noto & Bianchi, 2015). The externalisation process led by the recent spending review trends is pushing governments to enhance efficiency while using the best optimization level for resources compared to the public services provided (Levine, 1978;Pandey, 2010).…”
mentioning
confidence: 99%